Improving the Internships Quality in Supporting Vocational College Students' Job Search Success - Santosa, Dony Firman; Adil, Athira Setira; Wikansari, Rinandita; Oktariani, Erfina (Universitas Brawijaya, Indonesia, 2024)
Internships prepare students to enter the industry, business world, and world of work (IDUKA). Internships encourage improved job prospects, higher wages, and reduced skill mismatches. The purpose of this study is to analyze the influence of internship quality on students' career adaptability and students' job search success also to formulate strategic recommendations for improving the quality of apprenticeship programs. The population of this study is all alumni of Politeknik Ketenagakerjaan, Politeknik APP Jakarta and Politeknik STMI Jakarta who are recorded as already working. A total of 99 respondents were selected by purposive sampling then analyzed using SEM-PLS and the Analytic Hierarchical Process (AHP). The results of the study found that there is a positive and significant influence between internship quality on career adaptability, career adaptability on job search success, internship quality on job search success and internship quality on job search success through career adaptability. The most important alternative strategy for improving internship quality is setting up an internship mentoring program. Universities and companies must develop an internship curriculum for each internship position before setting up an internship mentoring programme.